Konversi Energi Termal Hasil Pembakaran Limbah Batang Jagung (Zea mays) Menjadi Energi Listrik Menggunakan Sistem TEG - Nur Safitri Madi; Asri Arbie; Muh Fachrul Latief (Transbahasa, 2025)
The increasing demand for electricity, environmental pollution, and global warming are major challenges today. One potential solution is the utilization of biomass as an alternative energy source. This study explores the conversion of agricultural waste, specifically corn stalks, into electrical energy using a Thermoelectric Generator (TEG) on a small scale. An experimental method was employed with series and Paralel configurations to analyze system efficiency. The results indicate that after 90 minutes, the maximum power output during supercapacitor charging was 0.684 W for the series configuration and 0.301 W for the Paralel configuration. Without supercapacitor charging, the power output was 0.4118 W for the series and 0.175 W for the Paralel configuration. In terms of converted energy, the series configuration produced 33.7 Wh, while the Paralel configuration generated 35.75 Wh. These findings suggest that although the series configuration is more efficient in generating peak power, the Paralel configuration yields a higher total energy conversion. This study provides insights into biomass utilization as a sustainable energy source in Gorontalo.